Review Article: A Structured Review of Semi-Presidential Studies: Debates, Results and Missing Pieces. Issue 3 (2nd July 2020) - Åberg, Jenny; Sedelius, Thomas
Abstract : This study maps the general lines of semi-presidential research with regard to theory, topics and methods. It identifies research gaps and provides recommendations for future studies. The review includes a general screening of 327 publications covering the period 1970–2015, and a close reading of sixty-five selected publications. The findings suggest that the inconsistent use of regime type definitions has limited the possibilities for generalizations. The study tracks the influence of some seminal articles, as well as the recent trend of focusing on the role and powers of the president. The article calls for more studies beyond Europe, and suggests that the field would benefit from including Historical and Normative Institutionalism. Finally, it suggests the need for studies on public administration that are relevant to the functioning of semi-presidential government.